2016
DOI: 10.1111/ejn.13440
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural benefits of multisensory processing in ferrets

Abstract: Enhanced detection and discrimination, along with faster reaction times, are the most typical behavioural manifestations of the brain's capacity to integrate multisensory signals arising from the same object. In this study, we examined whether multisensory behavioural gains are observable across different components of the localization response that are potentially under the command of distinct brain regions. We measured the ability of ferrets to localize unisensory (auditory or visual) and spatiotemporally co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…When performing the task, rats showed shorter reaction times in multisensory conditions. This result is consistent with what was observed in many previous studies conducted in both humans and animals [40][41][42][43]. Of especial relevance to our finding here, it has been shown that a task-irrelevant auditory stimulus could shorten the reaction time of responding to visual cues [44] and multisensory processing of both semantic congruent and incongruent stimuli could speed up reaction time [42].…”
Section: Discussionsupporting
confidence: 93%
“…When performing the task, rats showed shorter reaction times in multisensory conditions. This result is consistent with what was observed in many previous studies conducted in both humans and animals [40][41][42][43]. Of especial relevance to our finding here, it has been shown that a task-irrelevant auditory stimulus could shorten the reaction time of responding to visual cues [44] and multisensory processing of both semantic congruent and incongruent stimuli could speed up reaction time [42].…”
Section: Discussionsupporting
confidence: 93%
“…Fortunately, it turned out that ferrets can be readily trained to carry out sensory tasks. This species is increasingly being used to study aspects of visual (Garipis & Hoffmann, ; Von Melchner, Pallas & Sur, ; Zhou, Yu, Sellers & Fröhlich, ) and multisensory behaviour (Hammond‐Kenny, Bajo, King & Nodal, ; Hollensteiner, Pieper, Engler, König & Engel, ), and has been employed extensively in a range of auditory detection, discrimination and localization tasks (reviewed by Fritz, Elhilali, David & Shamma, ; Nodal & King, ).…”
Section: Experience‐dependent Plasticity In Developing Sensory Systemsmentioning
confidence: 99%
“…Further evidence that cue reliability may determine how multisensory spatial information is integrated is provided by the demonstration that co-located visual cues can both improve the accuracy of sound localization judgments (Bolognini et al, 2007; Tabry et al, 2013; Hammond-Kenny et al, 2017) and contribute to the suppression of echoes (Bishop et al, 2011). Adaptive changes in sound localization accuracy following manipulation of auditory spatial cues can take place, however, in the absence of visual feedback (Kacelnik et al, 2006; Carlile and Blackman, 2014; Zonooz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%